Film Indie Ã¢â¬ÅTanda Tanya (?)Ã¢â¬Â, Representasi Perlawanan, Pembebasan, dan Nilai Budaya - Belasunda, Riksa; Sabana, Setiawan (PANGGUNG, 2016)
ABSTRACTÃÂ The study was conducted in an effort to learn more about ÃÂ the notion that indie film as a representation ÃÂ of resistance ÃÂ against restrictions as well as a representation ÃÂ of liberation ÃÂ and democratization ÃÂ of post-reform ÃÂ media. Aa well as an effort to find out more about ÃÂ how the free interpretationÃÂ  ÃÂ of audienceÃ¢â¬â¢s ÃÂ on the filmÃ¢â¬â¢s text. The case study ÃÂ conducted through ÃÂ the research object ÃÂ indie film Ã¢â¬ÅTanda ÃÂ Tanya (?)Ã¢â¬Â. ÃÂ A qualitative ÃÂ research ÃÂ approach ÃÂ to cultural studies through ÃÂ interdisciplinaryÃÂ  ÃÂ researchÃÂ  method hermeneutic ÃÂ phenomenology with descriptive inter- pretative techniques. The filmÃ¢â¬â¢s text is a representation ÃÂ of resistance ÃÂ on the socio-political condi- tion of the New Order ÃÂ period are influencedÃÂ  by: (a) reform euphoria that created ÃÂ freedom; (b) the expression ÃÂ of which is contrary to the narrative ÃÂ of nation ÃÂ hegemony; (c) circulation ÃÂ of audio- visual media; (d) highlighted ÃÂ the efforts ÃÂ of local identity ÃÂ and local-global dialectic. ÃÂ In relation to the interpretationÃÂ  ÃÂ of the text contained cultural values; radical relativity ÃÂ and the plurality.ÃÂ Keywords: indie film, filmÃ¢â¬â¢s text, resistance and liberation, cultural valuesÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Penelitian dilakukan sebagai upaya untuk mengetahui lebih jauh anggapan bahwa film indie sebagai representasi perlawanan atas pembatasan sekaligus sebagai representasi pembebasan dan demokratisasi media pasca reformasi. Juga sebagai upaya untuk mengetahui lebih jauh bagaimana interpretasi bebas penonton atas teks film. Studi kasus dilakukan lewat obyek penelitian film indie Ã¢â¬ÅTanda Tanya (?)Ã¢â¬Â. Merupakan penelitian kualitatif dengan pendekatan cultural studies melalui metode penelitian interdisiplin fenomenologi hermeneutik dengan teknik deskriptif interpretatif. Teks film ini merupakan representasi perlawanan atas kondisi sosial-politik masa Orde Baru yang dipengaruhi oleh: (a) euforia reformasi yang menciptakan kebebasan; (b) ekspresi yang bertentangan dengan narasi hegemoni negara; (c) sirkulasi media audio-visual; (d) upaya menonjolkan identitas lokal dan dialektika lokal-global. Dalam kaitannya dengan interpretasi teks terdapat nilai- nilai budaya; relativitas radikal dan nilai pluralitas.ÃÂ Kata kunci: ÃÂ film indie, teks film, perlawanan dan pembebasan, nilai-nilai budaya